Human cell-adhesion molecule CD2 binds CD58 (LFA-3) with a very low affinity and an extremely fast dissociation rate but does not bind CD48 or CD59. - van der Merwe, P; Barclay, A; Mason, D; Davies, E; Morgan, B; Tone, M; Krishnam, A; Ianelli, C; Davis, S (1994)
CD2 is a T lymphocyte cell-adhesion molecule (CAM) belonging to the immunoglobulin superfamily (IgSF) which mediates transient adhesion of T cells to antigen-presenting cells and target cells. Reported ligands for human CD2 include the structurally-related IgSF CAMs CD58 (LFA-3) and CD48 as well as, more controversially, the unrelated cell-surface glycoprotein CD59. Using surface plasmon resonance technology, which avoids several pitfalls of conventional binding assays, we recently reported that rat CD2 binds rat CD48 with a very low affinity (Kd 60-90 microM) and dissociates rapidly (koff > or = 6 s-1) [van der Merwe, P. A., Brown, M. H., Davis, S. J., and Barclay, A. N. (1993) EMBO J. 12, 4945-4954]. In contrast, a study using conventional equilibrium binding methods reported a much higher affinity (Kd 0.4 microM) for human CD2 binding CD58 which suggested that the weak binding of rat CD2 to CD48 may not represent a typical CAM interaction. In the present study we have used surface plasmon resonance to obtain definitive affinity and kinetic data on the interactions of a soluble, recombinant form of human CD2 with soluble forms of CD58, CD48, and CD59. Binding of CD2 to CD58 was readily detected but we were unable to detect any direct interaction between CD2 and either CD59 or CD48 under conditions in which very low affinity interactions (Kd approximately 0.5 mM) would have been detected. In contrast to previous reports we found that human CD2 bound CD58 with a very low affinity (Kd 9-22 microM) and dissociated with an extremely fast dissociation rate constant (koff > or = 4 s-1). The association rate constant (kon) could not be measured directly but was calculated to be > or = 400,000 M-1s-1. Taken together, these results provide conclusive evidence that CAM interactions can have very low affinities and extremely fast dissociation rate constants.